Characteristics of Transportation Mode Selection in Manado Maritime City - Regina Lefrandt, Lucia Ingrid; Kumaat, Meike (Institut Teknologi Sepuluh Nopember, 2024)
The choice of transportation mode is one of the crucial aspects in urban transportation planning and development. Manado City as the economic and administrative center of North Sulawesi has experienced an increase in population and economic activity, which has an impact on transportation demand. This study aims to identify the characteristics of passengers in choosing transportation modes in Manado and to determine the factors that influence the choice of transportation modes. This research uses quantitative research methods. The results of the Structural Equation Modeling (SEM) test show the factors that influence the choice of transportation modes in Manado, namely travel costs, distance travel, and ease of access to modes. The CR value of travel costs to vehicle conditions is 7.456, the CR value of distance traveled to ease of access is 9.682, and the CR value of ease of access to online transportation is 4.654, conventional transportation is 8.282, and private vehicles is 7.365.